2020
DOI: 10.1177/1053825920973704
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of the Dynamic Nature of Psychological Ownership in a Classroom-as-Organization

Abstract: Background: Feelings of ownership play an important role in experiential education and are associated with several positive outcomes. However, researchers have yet to explore the dynamic nature of psychological ownership and its antecedents in experiential courses from the perspectives of the students. Purpose: The authors used the lens of psychological ownership theory to explore the experiences of students in an experiential learning setting. Methodology/Approach: In this study, the authors used repeated wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The study found that the college participants, JJS participants, the instructor, and the coordinator of JJS all recognised that the experience was elevated through relevant curriculum. Such curriculum was rooted in efforts to raise critical consciousness by applying deep oral and written reflection and modelling, encouraging authentic relationships between the participants at the community partner site and the college, and a consistent effort to redistribute power in all interactions (Cocieru et al 2021;Mitchell 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The study found that the college participants, JJS participants, the instructor, and the coordinator of JJS all recognised that the experience was elevated through relevant curriculum. Such curriculum was rooted in efforts to raise critical consciousness by applying deep oral and written reflection and modelling, encouraging authentic relationships between the participants at the community partner site and the college, and a consistent effort to redistribute power in all interactions (Cocieru et al 2021;Mitchell 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, participants have indicated that this was one of the best class experiences of their business school career and have acknowledged the role it has played in preparing them for a successful transition to the business world. Student enthusiasm about the upcoming theme often circulates in advance of registration deadlines, and the students enjoy multiple activities related to promotion and social media before and after the class meeting times, thus displaying ownership of the learning environment, as indicated in Cocieru et al (2021). "Bonus" experiences include having professional photographs taken as part of the experience, along with the opportunity to appear in university publications as they wish, while being captured performing many of the group activities in the course.…”
Section: Delivery In a Time-intensive Condensed Formatmentioning
confidence: 99%